Design and Development of an IoT-Based Escalator Control System Using WhatsApp as a Learning Medium at Makassar Aviation Polytechnic - Irfan; Andi.Muh. Kautsar Jeddawi. Bn; Andi Athaya Endra Zaki; Ahmad Gaffar (Indonesian Journal of Multidisciplinary Scientific Studies, 2025)
The limited practical laboratory facilities at Makassar Aviation Polytechnic, especially for the Airport Equipment course, force students to make direct visits to the airport to study equipment such as escalators. This condition not only hampers the effectiveness of learning but also adds to the cost and time burden. This research aims to design and test an Internet of Things (IoT)-based escalator control system integrated with WhatsApp application as an interactive learning media. The system is controlled through WhatsApp message commands using ESP32, which is connected to the SSR module, LCD, buzzer, and AC motor. The tool development was carried out using the Research and Development (R&D) method and tested using a black box testing approach. The test results show that all system components work optimally, and a survey involving 29 respondents showed an average effectiveness rate of 97.8%. The system proved to be easy to understand, responsive, and suitable for learning needs. Thus, this tool not only accelerates students' understanding of IoT-based automatic control systems, but also becomes an efficient solution to overcome the limitations of practicum facilities in the campus environment. This system also opens up the potential of utilizing popular communication platforms as a means of controlling engineering devices in the world of vocational education.